2018
DOI: 10.1111/eve.12952
|View full text |Cite
|
Sign up to set email alerts
|

Advanced imaging of an incomplete fracture and exostosis of the third metacarpal bone in a young Warmblood horse

Abstract: Summary A 5‐year‐old Hanoverian gelding with acute moderate right forelimb lameness underwent nuclear scintigraphy, which identified marked increase in radiopharmaceutical uptake of the proximomedial aspect of the right metacarpus. Ultrasonography and radiography identified sclerosis and exostosis of the proximomedial aspect of the metacarpal bone III in‐between the suspensory ligament and the second metacarpal bone, and presence of a suspected fracture. The owner requested euthanasia of the gelding, and post‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 25 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…; Werpy and Redding ; Isgren et al . ), the bone proliferation seems to follow a curvilinear path around the suspensory ligament. This curvilinear projection is present at the same proximal to distal location in all these cases.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…; Werpy and Redding ; Isgren et al . ), the bone proliferation seems to follow a curvilinear path around the suspensory ligament. This curvilinear projection is present at the same proximal to distal location in all these cases.…”
mentioning
confidence: 91%
“…It has been surmised that the region of injury is difficult to detect on physical examination because the injury occurs on the axial (inner) side of the splint, between the small metacarpal bone and the suspensory ligament in the same region highlighted by Isgren et al . (). It has been reported that histologically, the affected interosseous ligament usually consists primarily of chondroid tissue, whereas the normal interosseous ligament is primarily composed of dense white fibrous connective tissue.…”
mentioning
confidence: 97%
See 3 more Smart Citations